PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN ANGGOTA PADA CREDIT UNION BAHAGIA KABANJAHE - Silalahi, Esli; Silalahi, Donalson; Bangun, Dinalorena Br; Ritonga, Sinar (LPPM Universitas Katolik Santo Thomas Medan, 2025)
Service quality is something that is desired by customers in receiving products or services provided by service providers so that they are in accordance with customer expectations. While trust is the consumer's expectation that providers of goods and services can be trusted or relied on to fulfill their promises. This study provides empirical evidence of the influence of service quality and trust on member satisfaction at CU. Bahagia Kabanjahe. The population in this study was 13,441 people where the number of samples was 100 people. The analysis method used was multiple linear regression and conducted t-tests and F-tests. The results of the study showed that service quality and trust together (simultaneously) had a positive and significant effect on member satisfaction at CU. Bahagia Kabanjahe. Likewise, partially it shows that service quality and trust have a positive and significant effect on member satisfaction.